Visible light photoinitiating systems: Toward a good control of the photopolymerization efficiency - Ibrahim, A. (2010)
This paper discusses the photochemistry of three-component photoinitiating systems (3K-PIS) for free radical photopolymerization and the efforts made during the last decades to propose efficient systems applied to the laser imaging area. A special focus is devoted to a new 3K-PIS working in the green region. It is based on a pyrromethene dye which is reduced or oxidized by a coinitiator. A third redox component is used that leads to the recovery of the initial dye and the formation of additional initiating species, preventing a fast photobleaching of the dye. The beneficial effect on the photopolymerization rates and the final monomer conversion is clearly noticed. Laser flash photolysis was used to understand the reaction mechanisms, and detailed photopolymerization kinetics allow the study of polymeric network formation.